Transforming spaces: students innovate with technical drawing projects / Mohamad Zain Hashim and Muriatul Khusmah Musa - Hashim, Mohamad Zain; Musa, Muriatul Khusmah (Unit Penerbitan PKAPP, 2024)
In an impressive showcase of creativity and technical skill, students from the Technical Drawing course have unveiled a series of innovative projects aimed at repurposing a kindergarten building into various communityserving facilities. These projects, part of a larger assignment that combines practical skills with theoretical knowledge, were developed using Autodesk Revit software, illustrating the students' ability to tackle complex civil engineering problems. The assignment tasked students with planning a renovation project for an existing kindergarten, challenging them to convert it into a facility with a completely different purpose without altering the building's footprint, number of floors, staircases, or roof structure. Among the proposed repurposings were a religious school, an old folks' home, a homeless shelter, an orphanage, a medical clinic, a gymnasium, a selfservice laundrette, food outlets, retail outlets, and other imaginative conversions. This exercise not only tested the students' architectural and engineering skills but also their ability to envision spaces that respond to community needs.